To the question of application of combined calculation of the indexes of pollutant emissions impact when managing atmospheric air quality - M. V. Volkodaeva; Y. S. Kanchan (Юг России: экология, развитие)
The article looks into the methodology of combined calculation of the indexes of influence of pollutants’ emission and into the application of the results of such calculations when managing atmospheric air quality. It is emphasized that the atmospheric air, like no other component of the environment, requires a city-level management of activities aimed at air protection. Objectives for the air quality management at a city level are described, with the key requirements for the air protection taken into account and combined calculations applied.